TINGKAT PENDIDIKAN DAN PENDAPATAN ORANG TUA PADA PRESTASI AKADEMIK - Arlien Jeannete Manoppo; Friskilia I. Bolung (NUTRIX, 2019)
Academic achievement is a form of success of a student obtained from the learning process in schools and colleges, this is realized because of the role of parents based on education level and income. The purpose of this study was to analyze the relationship between education level and income of parents with academic achievement. The method used in the study was an analytic observational study with a cross sectional design, involving 85 respondents selected through consecutive sampling. The results of the study stated that the income of male parents was very high at 43.5%, the income of female parents was low at 28.2%, the education level of parents was medium (45.9% for men and 41.2% for women), student academic achievement is high (49.4%), there is no significant relationship between the level of education of parents and student academic achievement (p> 0.05), and there is a significant relationship between parents' income and student academic achievement (p <0.05). Thus, there is no significant relationship between the level of education of parents and the academic achievement of the Nursing Faculty of Klabat University students, but there is a significant relationship between parents' income and the academic achievement of the Nursing Faculty students of Klabat University. The addition of other variables related to academic achievement needs to be done to improve the results of this study.